Antidiarrheal Effectiveness Test of Moringa Leaf Infusion (Moringaoleifera L.) on Male Mice (Mus musculus) - Siti Saidah; Hartalina Mufidah; Shinta Mayasari (Indonesian Pharmacopeia Journal, 2025)
ABSTRACT Diarrhea is a digestive system disorder defined as having more than three bowel movements per day, characterized by changes in stool shape and consistency, as well as an increased water content in the stool compared to normal levels. Recent data from the 2022 Indonesia Nutrition Status Survey (SSGI) indicates that the prevalence of diarrhea stands at 10.2%, up from 9.8% in the 2021 SSGI results. Many people still view diarrhea as a minor illness, often leading to fatal outcomes in its management. Most synthetic anti-diarrheal medications can cause unwanted side effects, prompting the need for safer alternatives derived from natural sources. One such herbal plant, moringa leaves, is known to contain flavonoids with potential anti-diarrheal properties. This study aimed to evalute the optimal dosage 200, 400 and 800 mg/kgBW of Moringa oleifera L. Leaf infusion for its antidiarrheal efficacy in male Mus musculus exhibiting oleum ricini by induced diarrhea. This research uses a type of laboratory experimental study research using male white mice (Mus musculus) that have been induced by oleum ricini. The mice used were 20 and divided into 5 groups, namely: negative control group (CMC Na), positive control group (loperamid HCl), moringa leaf infusion treatment group with infusion doses of 200, 400 and 800 mg/KgBW. The parameters analyzed were frequency of diarrhea, stool consistency, stool weight and duration of diarrhea. The results of phytochemical screening of moringa leaf infusa show that moringa leaf infusa contains flavonoids, alkaloids and tannins. The results of the observation of the antidiarrheal effectiveness of moringa leaf infusa (Moringa oleifera L.) at the most optimal dose, namely the dose of 400mg/KgBW with the parameters of the average frequency of diarrhea 6.5 times with an average stool weight of 0.62 grams and the average duration of diarrhea is 95 minutes. The data obtained were analyzed by ANOVA at the 95% confidence level. Moringa leaf infusa (Moringa oleifera L.) has activity as antidiarrheal in male white mice (Mus musculus) induced by oleum ricini with the most effective dose is at a dose of 400 mg/KgBW.